FUNDAMENTAL FACTORS OF INDONESIAN SHARIA SHARE PRICE IN THE FINANCIAL SECTOR - Sufyati HS; Hanifah Hanifah; Sofia Maulida (International Journal of Social Science, 2023)
Islamic stocks are securities in the form of shares that have and do not conflict with Islamic principles in the capital market. Investment in Islamic stocks is currently experiencing quite significant developments, so investors are looking at it from the side of the growth of their stock prices. One of the factors that affect stock prices is fundamental factors. The fundamental factors in this study are described as independent variables, namely the Debt-to-Equity Ratio (DER), Net Profit Margin (NPM), and Earning Per share (EPS), while the dependent variable is the Indonesian Sharia Stock Price in the Financial Sector which is listed in the Indonesian Sharia Stock Index (ISSI). This study aims to analyze the effect of DER, NPM, and EPS on Indonesian Sharia Stock Prices in the financial sector listed in the ISSI Index. The research method used is quantitative descriptive with multiple linear regression data analysis. The results of this study show that the Debt-to-Equity Ratio has a negative and insignificant effect on Sharia Stock Prices. Net Profit Margin has a positive but not significant to Islamic Stock Prices. Earning Per-share has a negative and not significant to Islamic Stock Prices. The ability of the DER, NPM, and EPS variables to explain variations in changes in the stock price variable is only 10.5%, whereas the remaining 80.5% can be influenced by other variables not examined. The implication of this study is that investors in investing do not only consider fundamental factors but other factors that are very significant to fluctuations in Islamic stock prices.